Are glacial refugia hotspots of speciation and cytonuclear discordances? Answers from the genomic phylogeography of Spanish common frogs. Issue 5 (18th February 2020) - Dufresnes, Christophe; Nicieza, Alfredo G.; Litvinchuk, Spartak N.; Rodrigues, Nicolas; Jeffries, Daniel L.; Vences, Miguel; Perrin, Nicolas; Martínez‐Solano, Íñigo
Abstract: Subdivided Pleistocene glacial refugia, best known as "refugia within refugia", provided opportunities for diverging populations to evolve into incipient species and/or to hybridize and merge following range shifts tracking the climatic fluctuations, potentially promoting extensive cytonuclear discordances and "ghost" mtDNA lineages. Here, we tested which of these opposing evolutionary outcomes prevails in northern Iberian areas hosting multiple historical refugia of common frogs ( Rana cf. temporaria ), based on a genomic phylogeography approach (mtDNA barcoding and RAD‐sequencing). We found evidence for both incipient speciation events and massive cytonuclear discordances. On the one hand, populations from northwestern Spain (Galicia and Asturias, assigned to the regional endemic R. parvipalmata ), are deeply‐diverged at mitochondrial and nuclear genomes (~4 My of independent evolution), and barely admix with northeastern populations (assigned to R. temporaria sensu stricto) across a narrow hybrid zone (~25 km) located in the Cantabrian Mountains, suggesting that they represent distinct species. On the other hand, the most divergent mtDNA clade, widespread in Cantabria and the Basque country, shares its nuclear genome with other R. temporaria s. s. lineages. Patterns of population expansions and isolation‐by‐distance among these populations are consistent with past mitochondrial capture and/or drift in generating and maintaining this ghost mitochondrial lineage. This remarkable case study emphasizes the complex evolutionary history that shaped the present genetic diversity of refugial populations, and stresses the need to revisit their phylogeography by genomic approaches, in order to make informed taxonomic inferences.